PROBING INTO STUDENTS’ USE OF AUTOMATED FEEDBACK IN ESSAY REVISION: A CASE STUDY OF TWO CHINESE EFL LEARNERS - Wang Jian; Zhang Tengyao (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2022)
Automated feedback (AF) has been extensively investigated by L2 researchers, but in-depth research on English learners’ use of AF to revise their English essays is still limited. Moreover, whether there exist individual differences in essay revision remains underexplored. To address these gaps, this cross-sectional study, by adopting a qualitative research method, mainly reports on two Chinese EFL (English as a foreign language) learners’ use of the feedback provided by Pigai, an AWE (automated writing evaluation) system. First, both researchers analyzed learners’ different writing drafts to see where changes were made. Then, learners participated in a retrospective interview regarding their revision behaviors. The writing drafts and the interview data reveal individual differences between both writers’ revision behaviors. Specifically, one writer accepted only a tiny portion of Pigai’s suggestions. In contrast, the other not only took up automated feedback but actively made self-initiated revisions. Such differences might be attributed to their gender difference, English proficiency, interest and motivation levels in English learning, stances on automated feedback, and writing experiences in secondary school.